2014
DOI: 10.1128/jvi.01696-14
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Downregulates Transforming Growth Factor β2 To Promote Enhanced Stability of Capillary-Like Tube Formation

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent of Kaposi's sarcoma (KS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Interestingly, our results indicate that TGFβ2, but not TGFβ1, is suppressed by VEGF in HUVECs and that capillary morphogenesis is inhibited by TGFβ2 in these cells, specifically highlighting TGFβ2 as anti-angiogenic in our system. Interestingly, it has been recently shown that KSHV infection of endothelial cells also downregulates TGFβ2 [ 61 ], and given that KSHV upregulates VEGF, our proposed pathway of VEGF-regulation of miR-30b and its downstream effects on TGFβ2 is also supported by this finding. Importantly, our data indicates that cells with higher levels of miR-30b secrete more TGFβ2 and that these cells have higher levels of Smad2 phosphorylation indicating an active autocrine TGFβ signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, our results indicate that TGFβ2, but not TGFβ1, is suppressed by VEGF in HUVECs and that capillary morphogenesis is inhibited by TGFβ2 in these cells, specifically highlighting TGFβ2 as anti-angiogenic in our system. Interestingly, it has been recently shown that KSHV infection of endothelial cells also downregulates TGFβ2 [ 61 ], and given that KSHV upregulates VEGF, our proposed pathway of VEGF-regulation of miR-30b and its downstream effects on TGFβ2 is also supported by this finding. Importantly, our data indicates that cells with higher levels of miR-30b secrete more TGFβ2 and that these cells have higher levels of Smad2 phosphorylation indicating an active autocrine TGFβ signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…KSHV microRNAs (miRNAs) are highly expressed during latency and regulate diverse cellular pathways ( 33 ). Results of recent studies showed the association between in vitro angiogenic activities and KSHV miRNAs ( 34 , 35 ). To investigate whether KSHV miRNAs might mediate KSHV-induced angiogenesis in MSCa, we infected them with a mutant virus containing a deletion of a cluster of 10 pre-miRNAs, including pre-miR-K1-9 and -K11 (ΔmiR) ( 36 ) and established a long-term MSCa culture infected with this mutant KSHV (LTC-ΔmiRMSCa).…”
Section: Resultsmentioning
confidence: 99%
“…Infection of endothelial cells with KSHV plays an important role in viral dissemination and paracrine induction of angiogenesis in KS lesions. KSHV-infected endothelial cells share the characteristics of transformed endothelial cells, including cell proliferation, chemotactic migration, and invasion [ 16 , 17 ]. Furthermore, KSHV infection can upregulate various cellular signaling pathways to increase endothelial cell proliferation and vascular permeability during angiogenesis and vasculogenesis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%